Pasture characteristics of Panicum maximum cv. Tanzânia fertilized with nitrogen in the end of summer - Euclides, Valéria Pacheco Batista; Macedo, Manuel Cláudio Motta; Zimmer, Ademir Hugo; Medeiros, Rodrigo Narciso de; Oliveira, Marcelo Paschoal de (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the forage yield, morphological components and nutritive value of Panicum maximum cv. Tanzânia, with a second application of nitrogen fertilizer in March, at the end of summer. Maintenance fertilizer was 50, 17.5 and 33.2 kg ha-1 of N, P and K, respectively, applied annually, in November. Besides, in half of the area, an additional 50 kg ha-1 of N was applied, in March. The treatments were tanzânia pasture with two levels of nitrogen fertilization, 50 and 100 kg ha-1. The paddocks were divided in six plots, and submitted to a rotational grazing. Forage yield, percentages of the morphological components and nutritive value were evaluated. The accumulation rates of green dry matter and leaf dry matter, mainly in autumn, were greater for pastures that received 50 kg ha-1 of N additional in March. There were increases in the percentages of crude protein and in vitro organic matter digestibility, before and after grazing, after nitrogen application. The fertilization with 50 kg ha-1 per year of N was enough to keep forage yield stable during three years under grazing. The fertilization with additional 50 kg ha-1 per year of N, in March, decreased seasonal dependence of forage production, besides yielding forage with a higher nutritive value during autumn.